An Analysis of Students’ Writing Ability on Writing Descriptive Text in New Normal Era at Grade Eleven of SMAN 10 Padang - Riyanti Aulia Putri; Yuli Tiarina (Journal of English Language Teaching, 2022)
This research was conducted to analyze the ability of students on writing descriptive text in a new normal era through content, organization, vocabulary, language use, and mechanical aspect at students grade eleven of SMAN 10 Padang. This research used quantitative descriptive methods to analyze the students’ writing ability. The sample was taken by using simple random sampling of 57 respondents who were students. Data was obtained from writing tests done by the students in grade eleven and interviews with the English teacher of SMAN 10 Padang. The data is analyzed by combining Heaton's theory of assessment and Jacob's scale of writing. The result of the research concluded that students' ability in writing the descriptive text was at a good level with mean score in 67. Meanwhile, students' ability in writing content, language feature and mechanic were fair to poor. Then, students' ability in writing organization and vocabulary  was good to average.  The highest score from the aspect was  in organization aspect with the percentage of 74%. It concluded that students had difficulty in developing the content, students lack understanding of simple present tense structures, and errors in mechanics.  In addition. The interview result with the english teacher also explain some problem faced by the students in writing  such as difficult to organized the text because they do not understand the component of descriptive text and difficult to make a sentence.